(untitled) - Gent, Rachelle

The metabolism and receptor interactions of C11-oxy steroids: implications for hormonal homeostasis and pathophysiology (Stellenbosch : Stellenbosch University, 2024)
Thesis (PhD)--Stellenbosch University, 2024.